The effectiveness of nutrition education programme for primary school children - Abdul Talib, Ruzita; Mohd Abu Bakar, Wan Azdie; Mohd Noor, Ismail (Nutrition Society of Malaysia, 2007)
This study was conducted to determine changes in nutrition knowledge, attitude and practice of 8-year-old school children after receiving a nutrition education package. A total of 418 school children from urban and rural areas participated in this study. The intervention group consisted of 237 children while 181 children who did not receive the nutrition education package acted as controls. The nutrition education programme that was conducted for 3 weeks comprised of a video viewing session and a comic reading session followed by exercise questions as reinforcement for each session, and also classroom activities. Knowledge, attitude and practice questionnaires were distributed to the children before (pre-intervention) and after (postintervention) receiving the nutrition education programme. A follow-up visit was conducted six months after the programme had elapsed. The results obtained indicated that the nutrition knowledge score increased significantly in the intervention group from 48.3±13.2 at pre-test to 54.6±16.2 in post-test and 55.0±14.3 in follow-up test (p<0.05). The nutrition attitude score also increased significantly from 68.7±15.5 at pre-intervention to 72.6±15.0 and 74.7±15.8 during post-test and follow-up test respectively (p<0.05). However, the nutrition practice score had no significant improvement in both groups throughout the study period. There were no significant changes in the control group in knowledge, attitude and practice scores at pre, post and follow-up tests. In conclusion, this study showed that a good nutrition education programme had a positive impact whereby better nutrition knowledge, attitude and healthy eating habits in children were seen. It is hoped that the improvements would be sustained throughout their lives.